A study of preschool teachers' teaching experience and their attitude towards technology integration in teaching young children in Johor - Ong, Beverly Xin Kai (2024)
In today's rapidly shifting digital world, technology integration in Early Childhood Education (ECE) has become a critical component of current teaching and learning processes. As technology influences every part of our lives, it provides young learners with the skills and information they need to flourish in a digitally driven environment. Thus, examining preschool teachers’ attitudes towards technology integration in relation to their teaching experiences were essentially important since little emphasis given to investigate this topic in local ECE context. Therefore, the purpose of this study is to examine the preschool teachers’ attitudes towards the integration of technology in teaching young children and its relationship with years of preschool teachers’ teaching experience. This study is quantitative research by using correlational design that applied survey method in which a standardize questionnaires were distributed via Google form to 100 preschool teachers who work in Johor Bahru, Johor to collect data. The findings revealed that the preschool teachers’ attitude towards ICT is at the moderate level and there was a significant negative relationship between years of preschool teachers’ teaching experience on their attitudes towards the integration of technology in teaching young children (rho= -.880**, N=100, p=<.001). Higher preschool educators' teaching experience lowers their ICT teaching attitude. Conversely, less experience preschool educators are more optimistic towards using ICT to teach children. This study is beneficial for preschool educators, principals and preschool administrators to develop better strategies in integrating technology and provide continuous training to enhance preschool teachers’ attitudes and knowledge towards ICT especially with more experience preschool teachers. Future researchers are suggested to have larger sample size and employed random sampling method to increase the reliability of the study.